Exploration Collection and Conservation of Local Maize Germplasm of Nagaland - Kumar, Rakesh; Hangsing, Neivah; M, AO; Zeliang, P K; Deka, Bidyut C (Indian Journal of Hill Farming, 2016)
An exploration and collection of local maize germplasm was conducted in different district of Nagaland and a total of 38 maize accessions were collected, evaluated and conserved for documentation. The samples were in the form of maize kernels and seeds with various colour and size. Keeping these things in view field experiment was carried out during the kharif and rabi season of 2013-2015 to evaluate the yield potential of the local collected maize germplasm. Results revealed that the all the landraces collected differed significantly from each other in yield attributes and yield parameters. In terms of grain yield, the maximum yield was recorded with maize line Merangkong local-1 (5688.8 kg ha-1) and the minimum with Lampongonglak (1422.22 kg ha-1). Similarly, maize germplasm i.e. Merangkong local-1 (8988.45 kg ha-1) recorded the highest stover yield while the Lampongonglak (2247 kg ha-1) recorded the lowest stover yield.